A Comparative Study on Efficacy of Polymyxin B, Neomycin and Polymyxin B, Neomycin, Hydrocortisone in the Treatment of Otitis Externa at Nepal Medical College and Teaching Hospital, Kathmandu - Gupta, Mayuri; Aryal, S (Birat Journal of Health Sciences, 2017)
Introduction Acute otitis externa (AOE) is a common but preventable ear condition. Tenderness with movement of the tragus or pinna is a classic feature of otitis Externa. Polymyxin B, neomycin, hydrocortisone preparations are the choice for first-line therapy when the tympanic membrane is intact. This study atiempted to compare the efficacy of polymyxin B, neomycin and polymyxin B, neomycin, hydrocortisone in the treatment of otitis Externa. Objective To compare the efficacy of polymyxin B, neomycin and polymyxin B, neomycin, hydrocortisone in the treatment of otitis Externa. Methodology To evaluate the efficacy of polymyxin B, neomycin and polymyxin B, neomycin, hydrocortisone in the treatment of otitis Externa, a hospital based, randomized, prospective study was conducted in Nepal Medical College and Teaching Hospital (NMCTH), Atiarkhel, Kathmandu from August 2012 to May 2014. 70 outpatients suffering from otitis Externa who met the inclusion and exclusion criteria were included. Patients were randomized into group A and group B with lotiery system. Odd number patients were included in group A and even number patients in group B. Group A patients received pack soaked with ribbon gauge in polymyxin B, neomycin ointment and Group B patients received pack soaked with ribbon gauge in polymyxin B, neomycin, hydrocortisone ointment. The patients were called for follow up after 48 hours and 96 hours to assess the improvement on the basis of tragal and circumduction tenderness either present or absent (present 1 or absent 2). A decrease in the clinical signs and symptoms (i.e. tragal and circumduc_on tenderness) was noted. Absence of pain was considered as clinically cured. Results In comparison to polymyxin B, neomycin group, hydrocortisone group exhibited statistically significant effectiveness after 48 hours of treatment (p<0.05), but in cure rates after 96 hours, no statistical significant difference was observed between two groups (p>0.05). Conclusion Polymyxin B, neomycin, hydrocortisone group showed higher and faster cure rates than polymyxin B, neomycin group in the treatment of otitis Externa at 48 hours follow up. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 162-167